The Use Of Story Jumper Website To Improve Students Reading Comprehension Of Narative Texts - Lustina Anggriani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study investigates whether the use of the Story Jumper website can improve students' reading comprehension of narrative texts. A quasi-experimental design was applied to two eighth-grade classes at SMP Muhammadiyah Pagar Alam, comprising 62 students. The experimental group used Story Jumper as the learning medium, while the control group used a conventional method. Data were gathered using multiple-choice tests and analyzed with paired and independent sample t-tests in SPSS. While both groups showed improvement, the independent t-test revealed no significant difference between them (t_obt = 0.96 < t_table = 1.671; sig = 0.923), indicating that Story Jumper did not significantly affect comprehension. However, observations showed increased motivation and engagement in the experimental group, suggesting Story Jumper’s potential as a supportive tool.